Produktivitas Genotipe Padi Gogo Adaptif Naungan pada Kondisi Digenangi dan Kering - Edi Santosa (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2002)
Increase in utilization of upland rice tolerant to shade under plantation and commercial timber canopy. demands significant amount of seed become critical. The objective of this research was to study the productivity of shade-tolerant upland rice genotypes under flooded and dried cultivation. Research was conducted in the greenhouse of the Department of Agronomy, IPB, Bogor from September 1998 to March 1999. Random Complete Block (RCB) Design with two factors i.e. flood-dry and 12 genotypes of upland rice, namely Jatiluhur, Dodokan, TB 165E-TB-6, TB 13G-TB-2. ITA247, B7291D-SM-12,  B6926F-TB-l, B9484-F-TB-3, B9266F-PN-7-MR-2-PN-4, TBI77E-TB-30-B-2, B149F- MR-7. and TB35H-MR-3 was used. Genotypes were cultivated in plastic pots containing 10 kg media mix of soil and manure 9: I. Dry cultivation was performed with a two-day interval of watering; while flooding was done as in sawah field. Other maintenance such as weeding and fertilization were applied as in sawah cultivation. Treatments were replicated three times with two pots in each replicate. The result showed that flooding increased the number of tiller by 20% for the genotype B729ID-SM-12 (V6), B9484-F-TB-3 (V8), B9266F-PN-7-MR-2-PN-4 (V9), BI49F-MR-7 (V11), and TB35H-MR-3 (V12), increased biomass of top part 31.29 ± 29.02:% and roots 187. 91 ± 74. 16% for genotype TBI3G-TB-2 (V1), ITA247 (V5), B6926F-TB-1 (V-), B9484-F-TB-3 (V8), B9266F-PN-7-MR-2-PN-4 (V9), and TBI77E-TB-30-B-2 (V10), decreased the shoot root ratio by 53.10 ± 9. 70%; affected the number of productive tiller and the number of panicle 18.47± 51.04%; and increased the productivity up to 111.34 ± 123.19%. Based on a cluster analysis, three groups were proposed. A first group suitable for flooding were Jatiluhur (V1), TBI65E-TB-6 (V3), ITA247 (V5), B6926F-TB-1 (V-), B9484-F-TB-3 (V8). B9266F-PN-7-MR-2-PN-'4 (V9). and TBJ.77E-TB-30-B-2 (V10). A second group not suitable for flooding were Dodokan (V~, B7291D-SM-12 (V6), BI49F-MR-7 (V11), and TB35H-MR-3 (V12). A moderate genotype. TB 13G- TB-2 (V4). performed well in both cultivation methods was in the third group. Key words: Shading. upland rice, Flooding, Dry, Productivity